2019
DOI: 10.3233/icg-190118
|View full text |Cite
|
Sign up to set email alerts
|

Report on the Digital Ludeme Project

Abstract: This report summarises the discussions and conclusions of a recent Dagstuhl research meeting, in which the foundations of the new research field of Digital Archaeoludology were established. Starting with the ERC-funded Digital Ludeme Project, research in this field aims to use techniques from the field of Artificial Intelligence (AI), and other computational and data-driven techniques, to study traditional games. The primary goals include gaining improved insight into the ways games may have been played throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Rule variants, based on previous archaeological and historical knowledge of what those rules may be, are supplied, and the AI evaluates them by playing many games using this rule variant. This interplay between computers, archaeology and game design theory results in a new understanding of the range of viable rules for ancient board games (Soemers et al 2019).…”
Section: Playthings and Playgrounds Of The Pastmentioning
confidence: 99%
See 1 more Smart Citation
“…Rule variants, based on previous archaeological and historical knowledge of what those rules may be, are supplied, and the AI evaluates them by playing many games using this rule variant. This interplay between computers, archaeology and game design theory results in a new understanding of the range of viable rules for ancient board games (Soemers et al 2019).…”
Section: Playthings and Playgrounds Of The Pastmentioning
confidence: 99%
“…If we do so, recent board game studies and archaeogaming have shown that, to understand play, it is important to play. This can be done through replaying ancient games, as we did in our Past-at-Play Lab or as the AI in the Digital Ludeme project has been doing (Soemers et al 2019). We should also broaden the scope beyond board games and other obvious inferences of play and look at other places and things that evidence relations of commitment, attention and care as potential playgrounds.…”
Section: All Work and No Play?mentioning
confidence: 99%